Adaptability and cohesion of families in times of the COVID-19 pandemic - Carla Sílvia Fernandes; Bruno Magalhães; Silvia Silva; Beatriz Edra (Tehran University of Medical Sciences, 2021)
Background & Aim: This Covid-19 pandemic represents a threat and a crisis for families' well-being. According to the Olson Circumplex Model, this study aimed to assess the family functioning through the components of cohesion and adaptability of Portuguese families during this pandemic. Methods & Materials: This is a descriptive, exploratory, and correlational study. A non-probabilistic and convenience sample consisted of 376 people. Sociodemographic data, the family's characterization, the type of housing, the phase of the Vital Duvall cycle was collected from the participants, and FACES II was used to assess family cohesion and adaptability. The reliability of this instrument is high. The instruments for data collection were organized and sent through Google® forms, including the Informed Consent Form. The data were analyzed by SPSS-26 software using non-parametric tests were used for inferential analysis. Results: The results showed that 14,6% have a disengaged family cohesion; 7,4% have a very rigid dimension in family adaptability, and about the type of family, 6,1% have an unbalanced dimension. Conclusion: Although on average, the participants have a connected family cohesion and family flexible adaptability, many participants have extreme values, under which it will be necessary to intervene. It is a priority for family nursing to understand the experience of families living in this current social, economic, and health context.